Relation of Sustainable Development with Science Education and Human Needs and Greed - Agarwal, P.C.; Agarwal, I.B. (SCHOOL SCIENCE, 2017)
The challenge of meeting needs for human development while protecting the life support system on mother earth confronts scientists, technologists, policy makers and communities from local to global level. Many believe that people who have studied science play central role in sustainable development. While many other believe that human needs and greed eradicates the discrimination between them and those who have not studied science. Keeping in view the role of science education and the role of human needs and greed, this paper is an attempt to find out the relationship of the two independent variables—science education and humans’ future aspirations and plans for expenditure with one dependent variable—sustainable development. To carry out this study, the following standardised tools were used: (i) Scale for way of fulfillment of daily requirement (SWFDR) (ii) Scale for general awareness for the future consumption pattern (SGAFCP) The sample consisted of 90 (–45 studied science and –45 did not study science) persons belonging to middle class families in the age group of 21 to 60 years from Ajmer city. The data were collected using random sampling and execution of above tools. Using relevant statistical techniques, it is found that there is a significant mean difference between the groups of science educated and non-science educated persons on the scale SWFDR scores, on the basis of the obtained scores employing SWFDR, three groups were formed for higher, lower and average scores. No significant difference is found among these three groups on the basis of second scale (SGAFCP) scores. This shows that science education plays central role in sustainable development, however, humans’ needs and greed eradicate the difference between science educated and non-science educated persons.